Analisis Kemampuan Pemecahan Masalah Matematika pada Materi Bilangan Ditinjau dari Kemampuan Number Sense Siswa - Yunita Ramdani; Syahrul Azmi; Nourma Pramestie Wulandari; Laila Hayati (Griya Journal of Mathematics Education and Application, 2023)
This study aims to describe students' mathematical problem solving abilities in terms of number sense abilities. In this study, students were first given a number sense ability test and then given a problem solving ability test. Based on the results of the number sense ability test, it was found that 3 students had high number sense ability, 20 students had moderate number sense ability and 7 students had low number sense ability. After categorizing students into 3 categories of high, medium and low, then 2 students were selected in the high category, 2 students in the medium category, and 2 students in the low category. After selecting 6 subjects, an analysis was carried out on students' problem-solving abilities in terms of students' number sense abilities. Students with high number sense ability have high problem solving abilities. This is shown at the stage of understanding the problem, thinking of plans and implementing plans that have done well but are lacking in the stage of looking back. students with moderate number sense ability have high problem solving abilities. This is shown at the stage of understanding the problem, and carrying out the plan that has been done well but lacking in the stage of thinking about the plan and looking back. students with low number sense abilities have low number sense abilities. This is shown at the stage of thinking of plans, carrying out plans and when checking back on the results of students' work that they have not been able to do well.